Literatur Review: Analisis Determinan Kejadian Tuberkulosis pada Anak - Suryani Suryani; Memo Nababan; Aynal Paydah Harahap; Yolanda Sari; Erina Yolanda Br Hutabarat (JURNAL RISET RUMPUN ILMU KESEHATAN, 2026)
Tuberculosis (TB) remains a major global public health problem and is one of the leading causes of death after HIV/AIDS. This disease has a high transmission rate, especially among children. This study aims to identify and analyze the determinants contributing to the incidence of tuberculosis in children based on previous studies. The method used was a literature review, which analyzed scientific articles related to the determinants of TB in children. Articles were searched through databases such as Google Scholar, Crossref, and Sinta using related keywords. Of the five articles that met the inclusion criteria, it was found that a history of contact with an adult TB patient was the main factor in transmission in children. Children are highly susceptible to contracting TB germs transmitted through droplets from coughing or talking. In addition, BCG immunization can provide protection against TB infection in children by developing antibodies. A scoring system was used to examine the history of contact in children at risk. In conclusion, there is a significant relationship between history of contact and the incidence of TB in children. Therefore, it is important for adult TB sufferers who live with children to practice preventive behaviors, such as cough etiquette, wearing masks, and proper phlegm disposal.